Imidazolium Salts of Ruthenium Anionic Cyclopentadienone Complexes: Ion Pair for Bifunctional Catalysis in Ionic Liquids. Issue 11 (7th November 2019) - Cesari, Cristiana; Cingolani, Andrea; Teti, Martina; Messori, Alessandro; Zacchini, Stefano; Zanotti, Valerio; Mazzoni, Rita
Abstract : The reactivity of the dinuclear complex dicarbonyl[η 4 ‐3, 4‐bis(4‐methoxyphenyl)‐2, 5‐diphenylcyclopenta‐2, 4‐dienone] (2 ) with imidazolium salts has been studied using a library of variously functionalized imidazolium salts, and leading to a class of ruthenium anionic complexes of the type [dicarbonyl{η 4 ‐3, 4‐bis(4‐methoxyphenyl)‐2, 5‐diphenylcyclopenta‐2, 4‐dienone} (halide)Ru][1, 3‐disubsittuted‐imidazolium] (4 ) in the form of ion pair with imidazolium. The reaction is clean, general and quantitative and the complexes formed are stable to air and moisture both in the solid state and in solution. The ionic complexes 4 show affinity for ionic liquids and represent stable precursors of a catalytic active species, likely similar to those generated from Shvo catalyst, a well‐established homogeneous bifunctional catalyst for hydrogen transfer. Our approach allows the use of green ionic liquids (IL) as solvents, providing better control of catalytic reactions involving 4, and easier catalyst recycle. IL‐supported ionic pair catalysts exhibit interesting catalytic activity (up to > 99 % of conversion) in the transfer hydrogenation of a model compound such as 4‐fluoroacetophenone. The IL‐supported redox catalysts can be also recycled exploiting the biphasic nature of the system. The synthetic method here discussed represents a novelty within the field of IL‐supportation and is potentially useful for the heterogenization of the catalysts. Abstract : Bis(carbonyl) cyclopentadienone ruthenium complexes ion paired with variously functionalized imidazolium salts are suitable as bifunctional catalysts for transfer hydrogenation on a model compound, such as 4‐fluoroacetophenone, in ionic liquid media. The biphasic system allows recovery and recycling of the catalyst.